A coffee corridor for biodiversity and livelihoods: climatic feasibility of shade coffee cultivation in western Rwanda - Tom Reckmann; Marina Frietsch; Christoph Schwenck; Athanase Mukuralinda; Dula Wakassa Duguma; Joern Fischer (Trees, Forests and People, 2025)
Around the world, restoration activities are underway to halt and reverse ecosystem degradation. A key challenge is to identify restoration approaches that work for both people and nature – i.e. approaches that can sustain livelihoods as well as biodiversity. Here, we focused on a mosaic landscape in western Rwanda. The landscape features two strictly protected remnant patches of Afromontane rainforest (Gishwati and Mukura forests), which are of high conservation value, but are isolated from one another by some 30 km of smallholder farmland. Connecting Gishwati and Mukura forests would be valuable from a biodiversity perspective, but to date, it is unclear how this could be done in a way that is consistent with local people’s livelihoods. To that end, we modelled the climatic suitability for growing shade coffee in the area between Gishwati and Mukura forests. We systematically evaluated plausible scenarios of future climate change and found that much of the study area is already suitable for growing coffee, and will become increasingly suitable in the future. In addition, we identified a series of local species that could be used as shade trees. With the study area becoming increasingly suitable for growing coffee over the coming decades, and with suitable shade trees being native to the study area, we argue there is high potential for establishing a shade coffee corridor between Gishwati and Mukura forests. Such a corridor, in turn, could provide a win-win opportunity for biodiversity conservation and local people’s livelihoods.